Optimizing the construction of ecological networks in Beijing using a morphological spatial pattern analysis—minimal cumulative resistance model - Na, Yueqi; Hong, Zhujun; Ren, Siyuan; Huang, Kai (Frontiers in Environmental Science, 2024)
With the increasing fragmentation of landscapes caused by rapid urbanisation, constructing ecological networks strengthen the connectivity between fragmented habitat patches. As the capital of China, Beijing has a rapid development, resulting in a serious landscape fragmentation, and needing an urgent demand for this study to improve the ecological network system. In this study, we choose the elevation, slope, Normalized Difference Vegetation Index (NDVI) and land use data of Beijing in 2020 as the data use. Morphological spatial pattern analysis (MSPA) was used to identify ecological source areas for Beijing, Minimal cumulative resistance (MCR) and gravity models were used to construct ecological network, and stepping stones to improve it. The core area of Beijing had the highest proportion (96.17%) of all landscape types, forest accounting for 82.01% thereof. Ten core areas were identified as ecological source areas. Forty-five ecological corridors (8 major and 37 ordinary) were constructed. The ecological corridors are mainly concentrated in the middle and eastern regions where ecological mobility is limited. Constructing stepping stones would help uphold the region's ecological service functions and ecosystem balance. Twenty-nine stepping stones and 32 ecological obstacles were used to create the optimised ecological network, consisting of 171. The results provide an optimised ecological model for Beijing and a reference constructing ecological spatial networks for the sustainable development of ecological environments in high-density urban areas.